1984
DOI: 10.1118/1.595574
|View full text |Cite
|
Sign up to set email alerts
|

Determining P ion , the correction factor for recombination losses in an ionization chamber

Abstract: The 1983 AAPM protocol for the determination of absorbed dose from high-energy photon and electron beams recommends using Pion (the reciprocal of collection efficiency), as determined by the two-voltage technique, to correct for recombination losses in ionization chambers. Methods and data for the determination of ionization chamber collection efficiencies are scattered throughout the literature. The present work consolidates the available information, rectifies certain omissions, and provides several convenie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 0 publications
2
71
0
Order By: Relevance
“…The maximum deviation found in data provided by Weinhous and Meli (26) is 0.1%. The uncertainty of this component is therefore estimated at 0.06%.…”
Section: Resultsmentioning
confidence: 75%
“…The maximum deviation found in data provided by Weinhous and Meli (26) is 0.1%. The uncertainty of this component is therefore estimated at 0.06%.…”
Section: Resultsmentioning
confidence: 75%
“…The ion collection efficiency for several popular commercial ion chambers has been studied in pulsed and continuous photons using Boag's theory (20) . Weinhouse and Meli (15) provided a convenient method for determining Pion using the two‐voltage technique with a voltage ratio of two, which was also used in TG‐51 protocol for ion recombination correction. Bruggmoser et al (14) have proposed that the recombination correction factor depends only on dose per pulse and the chamber type, and it is not affected by radiation type or energy.…”
Section: Discussionmentioning
confidence: 99%
“…Although both studies have realized inaccurate estimation of ion recombination using the two‐voltage method, the two‐voltage method for the Pion measurement in the TG‐51 practice still can be used in this study because our study is focused on the relative comparison of ion recombination between the FFF and flattened beams. In addition, the two‐voltage method for the Pion measurement is used as a gold standard in many institutions 10 , 15 during X‐ray beam calibration procedures and the ratio of high and low operating voltage bias, which is at least two, can also be used in this study. Nevertheless, the two‐voltage method can introduce systematic error and a more accurate method can be obtained using the models suggested by DeBlois and Palmans 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Charge recombination has been studied extensively in the literature, 3 , 5 , 11 , 12 , 13 , 14 with authors focusing on either flat or nonflat beams. Kry et al (5) has considered both beam types and found the change (normalPion1) to be two to four times higher for FFF beams than for flat beams.…”
Section: Introductionmentioning
confidence: 99%